The Green Capability, Product Return, Value Chain Costing and the Adoption of Closed Loop Supply Chain in the Automobile Industry of Indonesia - Santhan Chayanon; Wijittra Srisorn (International Journal of Supply Chain Management, 2019)
The main objectives of the current study are to explore the nexus between green capability, product return, value chain costing, and the adoption of closed loop supply chain in the automobile industry of Indonesia. The role of product returns as a partial mediator in the CLSC adoption and recovery capability relationship indicates the absence of any direct relation among the two, thereby showing the significant role of manufacturer for encouraging towards product returns. Firms may be reluctant to invest in redeploying resources in the absence of adequate returns. The study has employed the SEM-PLS as a statistical tool to answer the research question. The findings of the study revealed the fact that the manufacturers in developing economies must understand the significant role of recovery capabilities in encouraging and influencing the CLSC system development and product returns, resulting in the reduction in ecological footprints. Presently, the Indonesian manufacturers are depending largely on traditional production methods with particular focus towards forward supply chain, having little or no consideration for recapturing, remanufacturing, and recycling of used items.